Employees’ perceived risk management in public procurement and finance: evidence in Malaysia / Azleen Ilias, Nasrudin Baidi and Erlane K. Ghani - Ilias, Azleen; Baidi, Nasrudin; K. Ghani, Erlane (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study evaluated employees’ perspectives about goal setting, the internal environment, information sharing, risk response, monitoring, risk assessment, control activities, and awareness of internal controls. Five hundred thirty-seven public workers responded to a questionnaire survey based on the Committee of Sponsoring Organizations (COSO) Enterprise Risk Management (ERM) (2004). In general, all employees in the public sector perceived procurement and risk management as high-risk sectors within the government’s procurement and payment divisions. This study demonstrated that employees comprehend risk management, although their understanding of internal controls is somewhat lacking. In addition, the employees voiced their concerns regarding the conflict of interest among review team members, the significant inertia, the numerous contact points, the preferred supplier indicators, the quantity of proposals, the ties between bidders that inhibited competition, and especially the size of bids. To achieve government goals, public personnel concurred that they must comprehend the systematic and procurement processes for all activities. This study implies that the employees may persuade top management to adopt a robust risk management strategy prior to establishing ministry and departmental goals, thereby aiding the government in enhancing risk management and combating corruption and the government’s Sustainable Development Goals (SDG) 12 and 16.